Research on the Optimal Layout Problem for NC Machining Based on Improved Genetic Algorithm - Wang Shuqing; Lei Lei; Wang Bing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In the process of NC machining, the optimization processing of graphic layout is a well-studied problem which has practical application value for improving the utilization rate of raw materials and saving the cost of production. In this paper, a new design of genetic algorithm (GA) is proposed for solving this problem. This improved genetic algorithm combines GA with the improved crossover operator and mutation operator. Moreover, the best individual preservation method is integrated into the algorithm. The improved genetic algorithm expands the search space and enhances the GA’s search capabilities. Furthermore, the maximum matching algorithm is proposed based on the lowest horizontal line algorithm, which effectively avoids blind elevating horizontal lines and improves the utilization rate of the lowest horizontal line. It is integrated with the improved genetic algorithm to solve the two-dimensional rectangular parts optimal layout problem which combines the advantages of two kinds of algorithms. The experimental results show that the algorithm can get a good optimization result.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3554